REKOMENDASI REKLAMASI BERBASIS LINGKUNGAN DI LUBANG BUKAAN BEKAS PERTAMBANGAN RAKYAT DI PERKEBUNAN JAGUNG DEARAH KABUPATEN SUMBAWA - Nofrohu Retongga; Sayidatina Hayatuzzahra; Roby Mardiyan Safitra; Rita Desiasni; Welly Handa Nuraga (Fakultas Teknologi Lingkungan dan Mineral - Universitas Teknologi Sumbawa, 2025)
The aim of this study is to create a descriptive model of environment-based reclamation recommendations for ex-mining land in the Sumbawa region that is easy to understand and consider. This research consisted of three stages: literature studies from previous researchers were used as a basic reference to strengthen the background and discussion in the research, especially with regard to environment-based reclamation engineering, mapping of open hole points from former community mining, and environment-based reclamation recommendation models. well and precisely in the corn plantation while still considering the initial shape of the topography. Effective reclamation to restore agricultural land damaged and with holes caused by mining without permits by providing recommendations in the form of a descriptive model includes backfilling of openings, planting trees, or revegetation, considering it for agrotourism, and economical fish-farming ponds.